Influence of the Maxillary Sinus on the Accuracy of the Root ZX Apex Locator: An Ex Vivo Study - Roula El Hachem; Elie Wassef; Nadim Mokbel; Richard Abboud; Carla Zogheib; Nada El Osta; Alfred Naaman (MDPI AG, 2019)
This study evaluated the accuracy of the Root ZX (J. Morita, Tokyo, Japan) electronic apex locator in determining the working length when palatal maxillary molar roots are in a relationship with the sinus. Seventeen human maxillary molars with vital pulp were scheduled for an extraction and implant placement as part of a periodontal treatment plan. The access cavity was prepared, and a #10 K file (Dentsply Maillefer, Ballaigues, Switzerland) was inserted into the palatal root using the Root ZX apex locator in order to determine the electronic working length (EWL); then, the teeth were extracted. To determine the real working length (RWL), a #10 K file was introduced into the root canal until its tip touched a glass plate. EWL and RWL were compared. Images reconstructed with CBCT (cone beam computerized tomography) revealed that eight palatal roots were related to the maxillary sinus, whereas nine were not. The results showed a significant difference between the EWL and the RWL of the palatal roots related to the sinus (p < 0.001). No significant difference was observed in measurements of roots not in contact with the sinus (p > 0.05). Within the study limitations, the reliability of Root ZX was influenced by the relationship of the roots with the maxillary sinus.